New insight into the composition of the lunar surface from SiO2 map - Chen, Wencong; Qiu, Denggao; Yan, Jianguo; Yi, Sihai (Frontiers in Astronomy and Space Sciences, 2025)
The distribution of FeO and TiO2 reveals mantle source characteristics and basaltic diversity, whereas SiO2 distribution is closely related to magma evolution and crustal differentiation. However, global studies on SiO2 remain limited. To address this gap, we combined the latest lunar sample data, Kaguya Multiband Imager spectra, and Christiansen Feature to develop a One-Dimensional Convolutional Neural Network (1D-CNN) for mapping lunar SiO2. The results reveal a clear spatial asymmetry in SiO2: high-latitude regions on the nearside show higher SiO2, while low-latitude regions exhibit lower values. Mare Tranquillitatis and Oceanus Procellarum have low SiO2 but distinct TiO2 variations, indicating different basaltic types and magmatic sources. The highlands are dominated by ferroan anorthosite, whereas the maria mainly consist of mafic to ultramafic rocks. Incorporating Chang’E-6 samples and Christiansen Feature data improved model accuracy. Future work on silicic volcanic rocks will further refine the global SiO2 map and deepen understanding of lunar crustal evolution.